Investigating Methods to Encourage Environmental Behaviour from Employees - Peel, Chris (2011)
There is a general agreement that greening organisations is of benefit to society. The green consumer movement is a rapidly growing market and describes the trends in the mood of consumer’s attitudes. As many green products now exist and companies regularly attempt to promote the green benefits of their product over their rivals, a logical step to gain a competitive advantage is to green the entire organisation yet there remains a distinct lack of literature that seeks to guide managers or develop theories to that end, especially on the topic of encouraging green behaviour from employees, who often hold the greatest influence over the environmental savings that can be achieved. As such, this study seeks to help to fill this void. A case study within a medical device manufacturer is conducted to view the methods managers seek to encourage green behaviour from their employees. It also adopts the employee perspective and seeks to discover what the employees of the company feel would encourage them to behave in a greener manner. Findings suggest that the techniques management feel are most appropriate to the situation are not the techniques that employees would most like to see deployed. Until these discrepancies are addressed, can we really expect to see meaningful greening of organisations?